Uniform Requirements for Manuscripts Submitted to Biomedical Journals: Writing and Editing for Biomedical Publication Updated October 2007 - ICMJE, The (Journal of Bangladesh Society of Physiologist, 2008)
Bangladesh Society of Physiologist (BSP) publishing this Uniform Requirements for Manuscripts Submitted to Biomedical Journals: Writing and Editing for Biomedical Publication - Updated October 2007 as a special article on good faith; as the ICMJE welcomes any organizations to reprint this document for non-profit educational purposes only. DOI:10.3329/jbsp.v2i0.987 J Bangladesh Soc Physiol. 2007 Dec;(2): 60-88.